Climate change versus land-use change—What affects the mountain landscapes more?. (January 2017) - Tasser, Erich; Leitinger, Georg; Tappeiner, Ulrike
Highlights: Modelling contrasting future LULC- and climate scenarios in an Alpine valley. Assessing the speed of LULC changes. Extreme scenarios for land abandonment and temperature rise reveal similar effects. All potential forest areas will be reforested over the next 700–800 years. The impact of LULC changes is strongly driven by past land-use intensities. Abstract: Land use and climate change are both strong drivers of landscape transformation. Using a representative valley of the Central Alps (Stubai Valley, Tyrol, Austria) we assess (1) the historical and likely future spatial patterns of land use/land cover (LULC), (2) the influence of temperature increase on the LULC distribution, and (3) the speed at which these changes will occur. Based on the historical landscape development and spatially explicit models, the effects of various land use and climate scenarios were modelled. Employing a pan-Alpine model, we were able to detect the temporal trajectory of spatial reforestation. The results show that land-use changes that already occurred during the last decades are responsible for the main future LULC changes (by secondary succession). Only an extreme land abandonment scenario and extreme climate scenarios (5 K temperature increase) would bring about similar changes in LULC distribution and expansion of the forested areas. While alpine grasslands, alpine pioneer formation and glaciers would shrink drastically, especially deciduous forests would spread. To a considerable degree, such changes might take place over the next 300 years. By contrast, the increase in forest areas triggered by temperature changes would be slower and longer termed (up to 700–800 years). The effects and intensity of land-use change in the investigated valley, that is comparable to many regions in the Alps, will be at least equally severe and responsible for transformation of the landscape as those of a projected temperature increase.